Reduced Neurobehavioral Impairment from Sleep Deprivation in Older Adults: Contribution of Adenosinergic Mechanisms - Landolt, Hans-Peter; Rétey, Julia V.; Adam, Martin (Frontiers in Neurology, 2012)
A night without sleep is followed by enhanced sleepiness, increased low-frequency activity in the waking EEG, and reduced vigilant attention. The magnitude of these changes is highly variable among healthy individuals. Findings in young men of low and high subjective caffeine sensitivity suggest that adenosinergic mechanisms contribute to inter-individual differences in sleep deprivation-induced changes in EEG theta activity, as well as optimal performance on the psychomotor vigilance task (PVT). In comparison to young subjects, healthy adults of older age typically feel less sleepy after sleep deprivation, and show fewer response lapses, and faster reaction times on the PVT, especially in the morning after the night without sleep. We hypothesized that age-related changes in adenosine signal transmission underlie reduced vulnerability to sleep deprivation in older individuals. To test this hypothesis, the combined effects of prolonged wakefulness and the adenosine receptor antagonist, caffeine, on an antero-posterior power gradient in EEG theta activity and PVT performance were analyzed in healthy older and caffeine-insensitive and -sensitive young men. The results show that age-related differences in sleep loss-induced changes in brain rhythmic activity and neurobehavioral functions are mirrored in young individuals of low and high sensitivity to the stimulant effects of caffeine. Moreover, the effects of sleep deprivation and caffeine on regional theta power and vigilant attention are inversely correlated across older and young age groups. Genetic variants of the adenosine A2A receptor gene contribute to individual differences in neurobehavioral performance in rested and sleep deprived state, and modulate the actions of caffeine in wakefulness and sleep. Based upon this evidence, we propose that age-related differences in A2A receptor-mediated signal transduction could be involved in age-related changes in the vulnerability to acute sleep deprivation.